Analisis Perbedaan Risk dan Return antara Saham Syariah dan Konvensional di Bursa Efek Indonesia - Lestari Lestari; Atty Erdiana (Jurnal Maksipreneur, 2021)
This study purposed to compare the Risk and Return between Islamic and conventional stocks listed on the Indonesia Stock Exchange. The object of this research is sharia and conventional stocks listed on the Indonesia Stock Exchange. The sampling method used in this study was purposive sampling with a sample size of 50 Islamic stocks and 50 conventional stocks. This research focused on the study of Islamic and conventional stock price data from 2015 to 2018. The analysis technique used to test the level of differences in risk and return in Islamic and conventional stock groups was the independent sample t-test. The results showed that there was no significant difference between the average return on Islamic and conventional stocks. Meanwhile, the results of the risk comparison of the two groups of stocks were heterogeneous (not the same) so that the risk of the two stocks cannot be compared.